Outcome of microsurgical clipping of ruptured intracranial aneurysms: An early experience - Lamichhane, Somraj; Tripathee, Sabin; Dev Bhandari, Ruchi (Nepal Journal of Neuroscience, 2022)
Introduction: Rupture of intracranial aneurysm is a catastrophic event with a mortality rate of 25% to 50%. Despite recent advances in endovascular techniques, microsurgical clipping is the standard modality of treatment due to its relative low cost and feasibility. We prospectively analyzed the cases of microsurgically clipped aneurysms with an aim to evaluate the overall outcome and the pretreatment variables predicting outcomes.Materials and methods: This is the prospective study of 15 consecutive microsurgical clippings of ruptured intracranial aneurysms conducted in the Department of Neurosurgery at College of Medical Sciences Teaching Hospital, Chitwan, Nepal from April 2018 to March 2020. Patients were followed up for at least three months and assessed according to modified Rankin Scale (mRS).Results: The mean age of patients was 55.47 years with female predominance. The most common location of aneurysms was Middle cerebral artery bifurcation (53%). Favorable outcome (mRS score 1 to 3) was achieved in 60% of patients whereas 40% had unfavorable outcome (mRS score 4 to 6). Poor Hunt and Hess at presentation and presence of vasospasm/infarction were associated with poor outcome. Overall mortality rate was 27%. Three patients required VP shunt whereas three patients each had vasospasm/Delayed ischemic neurological deficit (DIND) and intra-operative rupture.Conclusion: Microsurgical clipping of aneurysms is a standard treatment modality with good results despite recent advances in endovascular techniques. Favorable outcome can be achieved in patients with good Hunt and Hess grade at presentation and without clinical vasospasm/DIND.